The pinnacle reefs of Jabaloyas (Late Kimmeridgian, NE Spain): Vertical zonationand associated facies related to sea level changes. - Aurell, Marcos; Bádenas, Beatriz (Cuadernos de Geología Ibérica, 1997)
Sin resumen